PopStress: designing organizational stress intervention for office workers - Bao, Yanchi; Xue, Mengru; Gohumpu, Jennifer; Cao, Yumeng; Hu, Jun (Frontiers in Computer Science, 2023)
Excessive work stress on office workers will affect people’s health and work efficiency, and organizational stress management is becoming more and more critical. Current studies focus on the management of individual stress. The collective nature of stress and coping needs further exploration. This paper proposes the PopStress system, which converts the negative stress of an office group into the energy of a popcorn machine. When the organizational stress accumulates to the threshold , the popcorn machine will start making popcorn and attract office workers to take a break and eat. Through multisensory stimuli such as visual, audio, and olfaction, the system encourages natural and entertaining social stress-relieving behaviors within the office. 24 office workers were recruited and divided into 6 groups for the user study. The results showed that PopStress enables users to understand the collective stress status, and successfully relieved the individual’s physiological and psychological stress. This work provides insights into organizational stress management, health product design, and social design.